A reappraisal of sclerosing nodular and/or polypoid lesions of the gastrointestinal tract rich in IgG4‐positive plasma cells. Issue 6 (16th April 2020) - Chetty, Runjan
Abstract : Aims: To describe additional cases of nodular and polypoid sclerosing lesions of the gastrointestinal tract (GIT) that are associated with numerous IgG4‐positive plasma cells, review the pertinent literature to ascertain the relationship with systemic IgG4‐related disease, and provide a reporting framework for such lesions. Methods and results: Five new cases of sclerosing polyps or nodules were collected over a 10‐year period, occurring in four females and one male ranging in age from 32 years to 56 years (mean, 41.6 years). Patients were asymptomatic or had epigastric pain, and one had rectal bleeding. None had autoimmune or other obvious IgG4‐related disease, and serum IgG4 levels were normal. All were solitary nodules in the stomach (two cases), ileum, caecum, and rectum. Four lesions were submucosal and one was subserosal; all were well circumscribed, composed of hyalinised, keloidal fibrous tissue with lymphoplasmacytic inflammation. Obliterative phlebitis was not seen. Lineage‐specific immunomarkers were negative. In excess of 10 IgG4‐positive plasma cells per high‐power field were seen, and the IgG4/IgG ratios were >0.4. Conclusions: Very few IgG4‐related lesions in the tubular GIT are associated with disease at other sites and/or elevated serum IgG4 levels. The majority may represent a lesion in the spectrum of IgG4‐related disease. The use of the term 'IgG4‐positive nodule or polyp with probable histological features of IgG4‐related disease' is advocated for nodular and/or polypoid lesions in the GIT with ≥10 IgG4‐positive plasma cells in a high‐power field and an IgG/IgG4 ratio of >0.4.